Establishment of potent TCR-T cells specific for cisplatin-resistance related tumor-associated antigen, CLSPN using codon-optimization - Kanta Hori (20198286) (2024)
Adoptive T cell therapy, using T cell receptor-engineered T (TCR-T) cells and chimeric antigen receptor T (CAR-T) cells, is a potent immunotherapy option. Bladder cancer is a prevalent urological malignancy, particularly in cases of muscle invasion and metastasis, for which systemic therapy is crucial. Immunotherapy utilizing immune checkpoint blockade has been approved for bladder cancer treatment. The antitumor effect of an immune checkpoint blockade based on cytotoxic T cells (CTLs) and the patient’s immune status is essential. The chemotherapeutic drug cisplatin (CDDP) is a key drug in bladder cancer treatment. However, it has been shown to suppress T cells, making combination therapy with CDDP and immunotherapy difficult. To address this, we developed TCR-T cells specific for bladder cancer cells. In previous studies, we found that the tumor-associated antigen CLSPN is overexpressed in CDDP-resistant bladder cancer cells and that the antigenic peptide HLA-A*02:01/CLSPN1254–1262, encoded by CLSPN, could be targeted by a CTL clone. The TCR was cloned from the HLA-A*02:01/CLSPN1254–1262 specific CTL clone yc3. We also designed a codon-optimized TCR sequence using GeneArt® GeneOptimizer® (Opt TCR) and compared the TCR-T cells using the original TCR sequence (Ori TCR-T cells) and the codon-optimized TCR sequence (Opt TCR-T cells). Opt TCR-T cells exhibited higher TCR transduction efficiency, higher TCR expression levels, higher avidity, and greater cytotoxicity than did Ori TCR-T cells. These results suggest that HLA-A*02:01/CLSPN1254–1262 specific Opt TCR-T cells are promising candidates for CDDP combination therapy.